Geomorphological and Isotope-Geochemical Methods in Assessing the Gas Potential of a Territory (Using the Example of the Angara-Lena Oil and Gas Region) - Smirnov Aleksandr Sergeevich; Nourgaliev Danis; Chernova Inna Yur'evna; Ziganshin Eduard (Russian Journal of Earth Sciences, 2024)
The paper examines the geochemical method's effectiveness for assessing the gas potential of territories and prospecting for natural gas fields in combination with data on a territory's neotectonic activity obtained from the digital elevation model analysis in the Eastern Siberia area. Geochemical data include the content of methane and its homologues (C1 – C6), determined by gas chromatography in subsoil samples, as well as the carbon isotope ratio (δ 13C) of the detected methane, measured on an isotope mass spectrometer. The reconstruction of neotectonic activity areas was carried out using a modified morphometric method of digital elevation model analysis. Estimates of the macroscopic fracturing of the sedimentary cover, also caused by neotectonic activity, were obtained from the digital elevation model as the density of lines – primary linear objects expressed in relief, identified using the method of A. A. Zlatopolsky. The information obtained from the digital elevation model allows to identify areas where the probability of gas fields destruction is the highest. A joint analysis of isotope-geochemical data and information on the probable hydrocarbon deposits destruction makes it possible to assess the prospects for the territory's gas content, as well as identify promising areas.